Combination of anti-L1 cell adhesion molecule antibody and gemcitabine or cisplatin improves the therapeutic response of intrahepatic cholangiocarcinoma - Cho, Seulki (PLoS One, 2017)
Cholangiocarcinoma has a poor prognosis and is refractory to conventional chemotherapy and radiation therapy. Improving survival of patients with advanced cholangiocarcinoma urgently requires the development of new effective targeted therapies in combination with chemotherapy. We previously developed a human monoclonal antibody (mAb) Ab417 that binds to both the human and mouse L1 cell adhesion molecule (L1CAM) with high affinities. In the present study, we observed that Ab417 exhibited tumor targeting ability in biodistribution studies and dose-dependent tumor growth inhibition in an intrahepatic cholangiocarcinoma (Choi-CK) xenograft mouse model. Regarding the mechanism of action, Ab417 was internalized into the tumor cells and thereby down-regulated membrane L1CAM, and inhibited tumor growth by reducing tumor cell proliferation in vivo. Gemcitabine inhibited the tumor growth in a dose-dependent manner in the Choi-CK xenograft model. However, cisplatin inhibited the tumor growth moderately and not in a dose-dependent way, suggesting that the tumors may have developed resistance to apoptosis induced by cisplatin. Combined treatment with Ab417 and gemcitabine or cisplatin exerted enhanced tumor growth inhibition compared to treatment with antibody or drug alone. The results suggest that Ab417 in combination with chemotherapy may have potential as a new therapeutic regimen for cholangiocarcinoma. Our study is the first to show an enhanced therapeutic effect of a therapeutic antibody targeting L1CAM in combination with chemotherapy in cholangiocarcinoma models.